Comparing osteogenic effects between concentrated growth factors and the acellular dermal matrix - Luo Huang; Rui Zou; Jinquan He; Kexiong Ouyang; Zhengguo Piao (Sociedade Brasileira de Pesquisa Odontológica, 2018)
Abstract Concentrated growth factor (CGF) is an autogenuous product that contains highly concentrated number of platelets and can be derived from venous blood by selective centrifugation. It has been speculated that local growth factors in human platelets (insulinlike growth factor, IGF; transforming growth factor, TGF-b; platelet derived growth factor, PDGF) would enhance healing of grafts and also counteract resorption. The osteogensis effect of CGF and acellular dermal matrix (ADM) for alveolar cleft defects was evaluated in this study. Twenty alveolar cleft patients were divided randomly into two groups. One group underwent guided bone regeneration (GBR) using acellular dermal matrix film combined with alveolar bone grafting using iliac crest bone grafts (GBR group), while the other group underwent alveolar bone grafting combined with CGF (CGF group). Cone beam computed tomography (CBCT) images were obtained at 1 week and 6 months following the procedure. Using Mimics 17.0 software, the bone resorption rate and bone density improvement rate were calculated and compared between the two groups. Although not significant between ADM and CGF in bone resorption rate, the bone density improvement in cases with CGF(61.62 ± 4.728%) was much better than in cases with ADM (27.05 ± 5.607%) (p = 0.0002). Thus, CGF could be recommended to patients with alveolar cleft as a better choice.